Bone Fracture Incidence After Androgen Deprivation Therapy-Investigational Agents: Results From Cancer Therapy Evaluation Program-Sponsored Early Phase Clinical Trials 2006–2013 - Myint, Zin W.; Kunos, Charles A. (Frontiers in Oncology, 2020)
Introduction: Androgen deprivation therapy (ADT) is a primary treatment option for patients diagnosed with locally advanced-stage or metastatic prostate cancer. Androgen deprivation can be achieved either by radical orchiectomy or by medical castration using a gonadotropin-releasing hormone agonist. ADT has been linked to an initial 12-month loss of bone mineral density, a risk factor for weight-bearing bone fracture, and therefore, a confounding hazard for adverse event when patients are enrolled on early phase trials. To better understand the frequency of ADT-investigational agent-related bone fracture, we conducted a retrospective study of National Cancer Institute Cancer Therapy Evaluation Program (CTEP)-sponsored early phase trials to determine the number of fractures observed among enrolled prostate cancer patients. Patients and Methods: 464 locally advanced-stage or metastatic prostate cancer patients were identified among seven ADT-investigational agent trials conducted between 2006 and 2013. Demographic, co-morbidity, treatment, and adverse event variables were abstracted from CTEP databases and descriptive statistics were used. Results: 464 men had a median age of 64 years, were mostly white (90%), and had a performance status of 0 or 1 (98%). The number of new bone fractures occurring on or after ADT-investigational agent treatment was very low (4.6 per 1000 person-years). The median pretrial prostate specific antigen level was 29 ng/mL and most men (71%) had prostate cancer histopathology Gleason 7 score or higher. In these trials, 43 percent of men had bone only and 35 percent had bone and visceral metastatic disease. The most frequent grade 1 or 2 adverse events were fatigue (36%), hot flashes (27%), and anemia (17%). Grade 3 or higher adverse events were rare, with hypertension (3%) and hyperglycemia (3%) observed. Conclusions: Identifying bone health factors may still be relevant in selected early phase ADT-investigational agent trial patients, emphasizing the need for improved methods for capturing baseline bone health and studying ADT-investigational agent and concurrent medication interactions on bone health.